Contemporary use of anticoagulation in the cardiac catheterization laboratory: a review. Issue 3 (17th August 2021) - Klinkhammer, Brent J.; Nathan, Sandeep; Patel, Ankitkumar K.
Abstract : Anticoagulation during percutaneous coronary interventions has a rich history that has been shaped by several key clinical trials. The correct choice of anticoagulation during interventions can maximize patient outcomes and ensure a safe procedure. However, in some specific situations, anticoagulation may not be required at all. In this review article, we review the significant clinical trials and current guidelines regarding the use of anticoagulation in the catheterization laboratory and discuss the unique pharmacological aspects of the most commonly used agents, with an emphasis on the specific pharmacokinetic parameters that dictate how these agents are used and monitored. Finally, we discussed the future directions in anticoagulation therapy in coronary artery disease. This review serves as a robust synopsis of the clinical data for practicing clinicians and fellows in training.